2017
DOI: 10.1021/acs.orglett.7b01092
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed α-Stereoselective O-Glycosylation of O(3)-Acylated Glycals

Abstract: Pd(MeCN)2Cl2 enables the α-stereoselective catalytic synthesis of 2,3-unsaturated O-glycosides from O(3)-acylated glycals without the requirement for additives to preactivate either donor or nucleophile. Mechanistic studies suggest that, unlike traditional (η3-allyl)palladium-mediated processes, the reaction proceeds via an alkoxy-palladium intermediate that increases the proton acidity and oxygen nucleophilicity of the alcohol. The method is exemplified with the synthesis of a range of glycosides and glycocon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 48 publications
0
28
0
Order By: Relevance
“…Sau and Galan 353 also demonstrated that Pd(MeCN) 2 Cl 2 can be used to enable the α-stereoselective catalytic synthesis of 2,3-unsaturated O -glycosides from deactivated or “disarmed” glycals such as 315 without the requirement for additives to preactivate either donor or nucleophile. Mechanistic studies suggest that, unlike traditional (η3-allyl)palladium-mediated processes, the reaction proceeds via an alkoxypalladium intermediate (A) that increases the proton acidity and oxygen nucleophilicity of the alcohol under the reaction conditions (e.g., deactivated glycal and absence of anciliary ligands) ( Scheme 88 ).…”
Section: Transition Metal Catalysis Applied To 2-deoxyglycoside Synthmentioning
confidence: 99%
“…Sau and Galan 353 also demonstrated that Pd(MeCN) 2 Cl 2 can be used to enable the α-stereoselective catalytic synthesis of 2,3-unsaturated O -glycosides from deactivated or “disarmed” glycals such as 315 without the requirement for additives to preactivate either donor or nucleophile. Mechanistic studies suggest that, unlike traditional (η3-allyl)palladium-mediated processes, the reaction proceeds via an alkoxypalladium intermediate (A) that increases the proton acidity and oxygen nucleophilicity of the alcohol under the reaction conditions (e.g., deactivated glycal and absence of anciliary ligands) ( Scheme 88 ).…”
Section: Transition Metal Catalysis Applied To 2-deoxyglycoside Synthmentioning
confidence: 99%
“…The structure of glucoside 3a was confirmed by the 1 H NMR spectra where the anomeric proton (H1) appeared at δ 5.16 ppm (for glucal 1a it appears at δ 6.47 ppm) and the protons of the new double bond (H2, H3) appeared at δ 5.90–5.88 ppm [19]. The corresponding protons in the β-isomer appeared at δ 5.22 (H1) and δ 6.01 (H2, H3) [19,21].…”
Section: Resultsmentioning
confidence: 99%
“…The Ferrier rearrangement is one of the most useful processes to synthesize pseudo-glycosides in a direct and stereoselective fashion. Several classes of catalysts have been successfully applied in the Ferrier rearrangement including Brønsted acids [713], Lewis acids [1419], redox reagents [20] and metal catalysts [2123]. However, many of these catalysts have limited substrate scope, give variable selectivities and yields, require harsh reaction conditions and an excess amount of catalysts that are typically expensive, toxic and moisture/air sensitive.…”
Section: Introductionmentioning
confidence: 99%
“…Initial efforts using strong Lewis acid‐mediated Ferrier‐type glycosylation showed only formation of untractable mixture of compounds, presumably due to the instability of the anomeric centers in 12 (Scheme 3). Notably, employing Pd(MeCN) 2 Cl 2 (10 mol %) catalyst based upon Galan's work 14 generated 12 , albeit in low ~20% yield. Increasing the catalyst loading (30 mol %) under diluted condition in CH 2 Cl 2 delivered 12 in significantly higher 84% yield as an inseparable mixture of two anomers (α:β = 8:1) 15 .…”
Section: Methodsmentioning
confidence: 99%